Assessment and comparison of the effects of two techniques on hamstring flexibility - Navega, Marcelo Tavella [UNESP] (2014)
Introduction There are several stretching techniques that help increase flexibility, however, there are still questions regarding which method leads to the most effective gains. Objectives To assess and compare the effects of two stretching techniques, namely proprioceptive neuromuscular facilitation (PNF) and static stretching on the flexibility of hamstring muscles of young women. Methods The study sample consisted of 45 young women, mean age 20.45 (± 1.66),assigned to one of three groups: static stretching group (SSG, n = 15), proprioceptive neuromuscular facilitation group (PNFG, n = 15) and control group (CG, n = 15). Both SSG and PNFG carried out three weekly stretching sessions over a four-week period. The sit and reach and popliteal angle tests were used at the beginning and end of the intervention. Normally distributed data were analyzed using Student’s t-test, whereas data with non-normal distribution were analyzed using the Wilcoxon test, to compare initial and end measurements for each technique. Finally, we used the Mann-Whitney U test to compare both techniques with each other. A significance level of 5% (p < 0.05) was adopted. Results There was a significant increase in hamstring flexibility when analyzing the assessments and reassessments of both stretching protocols. Conclusions Both techniques were effective in increasing hamstring flexibility and there were no significant differences to indicate which one is better in increasing the flexibility of this muscle group.